IMPLEMENTATION OF FUZZY ANALYTICAL NETWORK PROCESS IN PRIORITIZING TRANSPORTATION PROBLEM - Dewi, Alina Cynthia (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2020)
The main goal of this research is to help decision maker in prioritizing transportation problems. Although numerous criteria were identified, the critical problems of transportation is less investigated. In order to fill this gap, this study was carried out to prioritizing the critical problems of transportation. The approach developed in this study implements fuzzy ANP to determine the weight for transportation problem criteria and sub criteria. As a result, the highest rank sub criteria was identified, that is â€œProfessionalismâ€ (0.203), followed by â€œPersonal vehicle preferencesâ€ (0.190) and â€œE-ticketâ€ (0.145). Although prioritize of transportation problems were identified, future research needed to develop the alternative strategy for developing transportation improvement strategies.